EVALUASI POLA SPASIAL TUBERKULOSIS DI BANYUMAS MENGGUNAKAN FUZZY SET BERBASIS SISTEM INFORMASI GEOGRAFIS - Mutia Nur Estri; Supriyanto Supriyanto (Universitas Jenderal Soedirman, 2009)
Tuberculosis prevention in Banyumas which still become problem is the owness of case finding of positive Tuberculosis victims. It is caused by lack of supporting aspect from community. For 2007 there are 4229 cases and 367 of them are active patients who take medical treatment. This research aim to for: a). to making a map of thematic which good for knowing pattern spreading of disease of TB in Banyumas, b). knowing factors having an effect on to spreading of disease of TB in Banyumas, and c). knowing subdividing pattern (regional clustering) pursuant to spreading of disease of TB in Banyumas. This research uses method of fuzzy set with approach of Geographical Information System.Results which are obtained from this research are: a) Tuberculosis event is significantly related to poverty. It is caused by low education level and occupation of Tuberculosis victim. b) Tuberculosis spreading is not related directly to population density, age, disease status of Tuberculosis victims and distance from medical facility. Spatial distribution pattern of Tuberculosis does not follow a certain pattern and c) Tuberculosis clustering tend to cluster at poor area in the city and spread follows the river flow.